Functional consequences of brain exposure to saturated fatty acids: From energy metabolism and insulin resistance to neuronal damage - Karina Sánchez‐Alegría; Clorinda Arias (Endocrinology, Diabetes & Metabolism, 2023)
Abstract Introduction Saturated fatty acids (FAs) are the main component of high‐fat diets (HFDs), and high consumption has been associated with the development of insulin resistance, endoplasmic reticulum stress and mitochondrial dysfunction in neuronal cells. In particular, the reduction in neuronal insulin signaling seems to underlie the development of cognitive impairments and has been considered a risk factor for Alzheimer's disease (AD). Methods This review summarized and critically analyzed the research that has impacted the field of saturated FA metabolism in neurons. Results We reviewed the mechanisms for free FA transport from the systemic circulation to the brain and how they impact neuronal metabolism. Finally, we focused on the molecular and the physiopathological consequences of brain exposure to the most abundant FA in the HFD, palmitic acid (PA). Conclusion Understanding the mechanisms that lead to metabolic alterations in neurons induced by saturated FAs could help to develop several strategies for the prevention and treatment of cognitive impairment associated with insulin resistance, metabolic syndrome, or type II diabetes.